(untitled) (Zien Journal of Social Sciences and Humanities, 2025)
The concept of economic culture occupies a pivotal position in understanding the development of human civilization and societal progress. It embodies the synthesis of decision-making processes related to the formation and rational use of scarce resources to satisfy the limitless needs of society. This notion, rooted in the classical political economy of Alfred Marshall and further developed through institutional economic theories such as those of Douglas North, offers fertile ground for a philosophical analysis of the underlying principles shaping economic behavior and culture.